New species and records of Orchidaceae from Costa Rica. II - Karremans, Adam; Bogarín, Diego; Fernández, Melania; Smith, Christina; Blanco, Mario (Lankesteriana: International Journal on Orchidology, 2012)
After the publication of the most recent and comprehensive treatment of the Orchidaceae in the Manual de Plantas de Costa Rica, new species continue being discovered in the country on a regular basis. Novelties in Acianthera, Epidendrum, Lepanthes, Masdevallia, Pleurothallis, and Specklinia are discussed. We present eight new records including the reconsideration of Epidendrum concavilabium (as different from E. circinatum), and the first record of the genus Epistephium (E. ellipticum) for the country. Three new taxa, Epidendrum alieniferum, Epidendrum × sandiorum (a putative natural hybrid between E. oerstedii and E. ciliare) and Lepanthes kabebatae are described.